2012
DOI: 10.19030/jabr.v28i2.6845
|View full text |Cite
|
Sign up to set email alerts
|

Digital Analysis Of Sales And Industry Partition: An Examination Of U.S. Public Companies

Abstract: <span style="font-family: Times New Roman; font-size: small;"> </span><p style="margin: 0in 0.5in 0pt; text-align: justify; mso-pagination: none;" class="MsoNormal"><span lang="EN-GB" style="color: black; font-size: 10pt; mso-themecolor: text1; mso-ansi-language: EN-GB; mso-bidi-font-style: italic;"><span style="font-family: Times New Roman;">Previous studies have shown that companies' managers tend to round-up reported earnings (Carslaw, 1988; Thomas, 1989; Niskanen &amp; Kel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
1
1
0
Order By: Relevance
“…But once cannot consider this to be a rounding behavior because we do not observe significantly more zeros as second digits than what could be expected by mere chance according to Benford's law. This finding is consistent with the prior studies of Jordan, Clarke, and Hames (2009) and Geyer (2012), who choose the same control variable. The two studies did not find rounding behavior in the total assets data set.…”
Section: Methodssupporting
confidence: 91%
“…But once cannot consider this to be a rounding behavior because we do not observe significantly more zeros as second digits than what could be expected by mere chance according to Benford's law. This finding is consistent with the prior studies of Jordan, Clarke, and Hames (2009) and Geyer (2012), who choose the same control variable. The two studies did not find rounding behavior in the total assets data set.…”
Section: Methodssupporting
confidence: 91%
“…Al -Darayseh et al (2000) documented the rounding-up behavior in case of reported earnings of companies listed in Istanbul Stock Market. Geyer (2012) studied the frequency of occurrence of zero in the second digit of reported sales and documented the existence of rounding-up behaviors in reported sales of US public companies. Darayseh et al (2010) demonstrated income enhancement in reported earnings of Gulf Cooperation Council (GCC) firms.…”
Section: Prior Research and Hypothesismentioning
confidence: 99%